Arsenic Induces Continuous Inflammation and Regulates Th1/Th2/Th17/Treg Balance in Liver and Kidney In Vivo - Duan, Xiaoxu; Xu, Guowei; Li, Jinlong; Yan, Nan; Li, Xin; Liu, Xuping; Li, Bing (Mediators of Inflammation, 2022)
Numerous studies on arsenic-induced hepatonephric toxicity including cancer have been reported. Given that chronic inflammatory response and immune imbalance are associated with oncogenesis, we investigated whether arsenic could influence the hepatic and nephritic expression of inflammatory factors and the differentiation of T cells. Mice were exposed to NaAsO2 (0, 25, and 50 mg/L) for 1 and 3 months. Our data showed the destruction of the structure and inflammatory infiltration in the liver. The arsenic markedly increased the activity of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The myeloperoxidase (MPO) activities increased in the liver at 25 and 50 mg/L arsenic for 3 months as well as in the kidney at both 1 and 3 months. An increased expression of inflammatory indicators (IL-1β, IL-12, and TNF-α) at 25 and 50 mg/L arsenic for 1 and 3 months in the liver and kidney, as well as IL-1β in the liver for 3 months and in the kidney at 50 mg/L for 1 and 3 months were demonstrated in our experiments. Besides, a definite tendency toward Th1/Th17 cytokines in the liver while Th2/Th17 cytokines in kidney was also observed by arsenic. Moreover, arsenic enhanced the expression of MAPK/Nrf2/NF-κB signaling molecules. In conclusion, the results of the study suggested that arsenic induces continuous immune-inflammatory responses in the liver and kidney.